A Brief Review of High Efficiency III-V Solar Cells for Space Application - Li, J.; Aierken, A.; Liu, Y.; Zhuang, Y.; Yang, X.; Mo, J. H.; Fan, R. K.; Chen, Q. Y.; Zhang, S. Y.; Huang, Y. M.; Zhang, Q. (Frontiers in Physics, 2021)
The demands for space solar cells are continuously increasing with rapid development of space technologies and complex space missions. The space solar cells are facing more critical challenges than before: higher conversion efficiency and better radiation resistance. Being as the main power supply in spacecraft, III-V multijunction solar cells are the main stream for space application nowadays due to their high efficiency and super radiation resistance. In multijunction solar cell structure, the key to obtain high crystal quality and increase cell efficiency is satisfying the lattice matching and bandgap matching condition. New materials and new structures of high efficiency multijunction solar cell structures are continuously coming out with low-cost, light-weight, flexible and high power-to-mass ratio features in past years. In addition to the efficiency and other properties, the radiation resistance is another sole criterion for space solar cells, therefore, radiation effects of solar cells and radiation damage mechanism is a widely studied field for space solar cells over decades. This review briefly summarized the research progress of III-V multijunction solar cells in recent years. Different types of cell structures, research results and radiation effects of these solar cell structures under different irradiation conditions are presented. Two main solar cell radiation damage evaluation models, the equivalent fluence method and displacement damage dose method, are introduced.